¨Poblaciones y porcentajes de polinización de Forcipomyia spp en el cultivo de cacao, en época lluviosa en la Zona de San José del Tambo ¨. - Gaibor Gómez, Jessica Lucia (2018)
VIII. SUMMARY The purpose of this research was to evaluate the population and pollination percentage of Forcipomyia spp. In the cocoa crop. The present investigation was carried out in the cacao farms, "Las Tres Marias", "La Teresita", "Rancho Mari Carmen", and "La Julita", located in the San José del Tambo parish, Chillanes Canton, Province of Bolívar, properties of the gentlemen, Luis Colina, German Robledo, María del Rocio Hinojosa Guanulema and Juan Freire, It is geographical location corresponds to 300 meters above sea level: Latitude: 9784 279 N and Longitude: 700 111 E, which has a humid sub-tropical climate, with an average annual temperature of 24 ° C, annual precipitation of 2,250 mm / year, relative humidity of 75% and low luminosity. Weekly the populations of Forcipomyia sip were evaluated and the percentage of pollination of this insect in 25 flowers per plant of each farm. The flowers were collected from the stem and branches of the plant were transferred to the ENTOMOLOGIA laboratory of the FACULTY OF AGRICULTURAL SCIENCES OF UTB, to observe them and establish the population level of the mosquito and the percentage of pollination. The results obtained indicate that the largest population of Forcipomyia spp and the percentage of pollination was obtained at Rancho Mari Carmen farm where no insecticide was used. In general, the largest population was obtained in the week 07/03/2018 and the smallest population was obtained in the week 04/04/2018. The population of Forcipomyia varied from 2.93 to 2.72. And the percentage of pollination varied from 11.70 to 10.85. Based on these conclusions, the following is recommended in this trial: Do not use insecticides that affect the population of Forcipomyia spp.